2016
DOI: 10.1016/j.physd.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A principle of similarity for nonlinear vibration absorbers

Abstract: This paper develops a principle of similarity for the design of a nonlinear absorber, the nonlinear tuned vibration absorber (NLTVA), attached to a nonlinear primary system. Specifically, for effective vibration mitigation, we show that the NLTVA should feature a nonlinearity possessing the same mathematical form as that of the primary system. A compact analytical formula for the nonlinear coefficient of the absorber is then derived. The formula, valid for any polynomial nonlinearity in the primary system, is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…It is worth noting that the vectorŨ 0 is unknown and is normalized by the third equation so thatŨ 0 -0. At this point, we can summarize the number of unknowns and equations of (22). We have:…”
Section: Limit Point Continuationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the vectorŨ 0 is unknown and is normalized by the third equation so thatŨ 0 -0. At this point, we can summarize the number of unknowns and equations of (22). We have:…”
Section: Limit Point Continuationmentioning
confidence: 99%
“…For instance, Habib and Kerschen use in Ref. [22] a perturbation method coupled to the HBM in order to analytically predict resonance peaks and establish some design rules about of the NLTVA. Some numerical methods are proposed to accurately predict amplitude resonance peak of a nonlinear system.…”
Section: Introductionmentioning
confidence: 99%
“…Febbo and Machado [12] explored the potential of using a nonlinear absorber with a saturation nonlinearity for vibration mitigation of a nonlinear primary oscillator possessing a cubic stiffness. Habib et al [13], Detroux et al [14] and Habib and Kerschen [15] stated that nonlinear https://doi.org/10.1016/j.ymssp.2019.07.005 0888-3270/Ó 2019 Elsevier Ltd. All rights reserved. stiffness k 2 is placed in parallel to the passive mount.…”
Section: Introductionmentioning
confidence: 99%
“…Although it exhibits a simple form, a variety of physical examples can be dynamically characterised by the Duffing equation such as pendulum dynamics [29], beam buckling [30], cable dynamics [31] and nonlinear isolators [32,33]. Using the NPPF controller for vibration mitigation of a Duffing oscillator can be considered as an active anti-vibration approach developed based on the principle of similarity as proposed in [13][14][15], since the NPPF controller possesses the same nonlinearity as the primary structure. Therefore, the optimisation process is sequentially performed in two steps.…”
mentioning
confidence: 99%
“…An attempt to eliminate this undesired phenomenon demonstrated that IRCs can be avoided if the absorber has a properly-tuned piecewise-quadratic damping characteristic [40]. Similarly, the nonlinear tuned vibration absorber (NLTVA), possessing both a linear and a nonlinear elastic force characteristic, can present an IRC that limits its range of operation [41,42]. A numerical procedure exploiting bifurcation tracking allowed to define regions of appearance of the IRC [43].…”
mentioning
confidence: 99%